1988
DOI: 10.1071/bi9880069
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Reproduction in Sheep and its Control by Photoperiod

Abstract: Seasonality of the reproductive cycle in sheep is a general phenomenon for mid-latitude breeds. The proximal part (breeding season) and also partially distal part (end of gestation and beginning of lactation) of this cycle is controlled by photoperiod, whatever the form of light regimens. Data are presented which indicate that male and female do not necessarily have the same photoperiodic sensitivity. Gonadal stimulation in the ram starts 1'5-2 months earlier than in the ewe under annual variations. Photoperio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
6

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 56 publications
3
41
0
6
Order By: Relevance
“…The difference of 0.66 kg in average BWT between spring (April) and autumn (September) lambs in the present study was similar to seasonal effects on BWT reported by others (Al-Shorepy and Notter, 1998;Jenkinson et al, 1995;McCoard et al, 1996;Morris et al, 1993;Ortavant et al, 1988;Reid et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The difference of 0.66 kg in average BWT between spring (April) and autumn (September) lambs in the present study was similar to seasonal effects on BWT reported by others (Al-Shorepy and Notter, 1998;Jenkinson et al, 1995;McCoard et al, 1996;Morris et al, 1993;Ortavant et al, 1988;Reid et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…Among the environmental factors, season was found to have an effect on BWT with lambs born in the autumn being smaller than spring-born lambs (Al-Shorepy and Notter, 1998;Jenkinson et al, 1995;McCoard et al, 1996;Ortavant et al, 1988;Reid et al, 1988). Seasonal effects on BWT of lambs can be attributed to changes through the year in photoperiodic effects (Ortavant et al, 1988), nutritional status of the ewe (Redmer et al, 2004) where ewes gestate in the summer and fed on pasture may experience lower food intake, and heat load (Shelton and Huston, 1968) which can be high during the summer. In addition, seasonal variation in gestation length (Jenkin and Young, 2004) may also be associated with seasonal variation in BWT.…”
Section: Introductionmentioning
confidence: 94%
“…In sheep [33], goats [34], deer [35] and horses [36-38], the annual reproductive season is synchronized by photoperiod through melatonin secretion. In mares, the date of first ovulation can be advanced by about two months by exposure to an artificial photoperiod in winter [36,37,39].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in testis size has been linked to environmental factors such as social dominance, social organization and seasonal changes across numerous species. Specifically, laboratory and field studies show that testes weights are significantly higher in dominant males as compared to subordinates (Kruczek & Styrna 2009; Maruska & Fernald 2011; Setchell & Dixson 2001), are significantly higher in animals that engage in sperm competition as compared to monogamous species (Awata et al 2006; Harcourt et al 1981; Simmons and García-González 2008), and can be positively influenced by long photoperiods (Ortavant et al 1988; Delgadillo et al 2004). …”
Section: Introductionmentioning
confidence: 99%